Gamma activity in Tigris river water and Rustumai wastewater treatment plant - R. Al-Ani, Rana; A. Amin, Sahar (International Journal of Physical Research, 2020)
The activity level of 226Ra, 232Th and 40K radionuclides at selected locations of Tigris River and Rustumai water treatment plant (before and after treatment) has been determined by using NaI(Tl) gamma spectrometry. The results show that the total average activity values were 44.3Bq kgâˆ’1 and 789.6Bq kgâˆ’1 for 226Raand 40K, respectively. These values are higher than the world recommended values given by UNSCEAR, while the total activity concentration of 232Th was within the world recommended value of 30 Bq.kg-1. Radiological hazard indices such as: radium equivalent activity in Bq.kgâˆ’1, annual equivalent dose in Sv.yâˆ’1, external and internal hazard indexes, representative gamma index, dose rate in nGy.hâˆ’1 and annual effective dose equivalent (outdoor and indoor) in mSv.yâˆ’1 were calculated. The calculated indices were below the world recommended values, hence they have no serious effects on people health and environmental species and the Tigris River water can be considered un-harmful for the environment and humans as they are within the world median limits. In the case of Rustumai wastewater treatment plant samples for untreated and treated samples, the average activity concentrations of the three radionuclides were higher than the world recommended values.Â Â